Carbohydrate chemistry. Chemical and Biological Approaches - Rauter A. P. Amelia Pilar; Lindhorst T. K. Thisbe (A Specialist Periodical Reports Vol. 39)
The Chemistry: Chemical and Biological Approaches, glycochemistry and glycobiology have been combined to demonstrate the contribution of organic chemistry, biological and biochemical expertise to the increasingly important field of glycomics. The first chapter is dedicated to the radical bromination of sugars, involving a broad range of substrates and their transformations, clearly demonstrating the synthetic utility of this reaction and the uniqueness of carbohydrates as starting materials, leading to a wide variety of molecular tools for chemical glycobiology. While the first chapter is dedicated to organic synthetic approaches, the second one illustrates the importance of enzymatic and chemoenzymatic syntheses for the production of heparin. Recent developments on synthetic glycolipids as ligands and inhibitors of mycobacterial cell wall component biosynthesis and functions are described in chapter 3 and the next chapters deal with carbohydrate processing enzymes and their inhibitors. The design and synthesis of glycosyltransferase and glycosidase inhibitors is revised, paying particular attention to imino sugars and to carbohydrate epoxides as key intermediates for inhibitor synthesis. An overview of the glycosidase metabolic changes in diabetes is presented and a survey of the most efficient and selective inhibitors of hexosaminidases, which are implicated in neurodegenerative disorders, is also given. A chapter is devoted to the interesting area of surface binding sites in carbohydrate active enzymes. Last but not least, a review of the X-ray crystallography of lectins completes the volume as the final chapter.